THE INFLUENCE OF GREEN ACCOUNTING, CORPORATE SOCIAL RESPONSIBILITY AND PROFITABILITY ON FIRM VALUE - Ake Dahlia; Imam Hadiwibowo; Mohammad Taufik Azis (Jurnal Ekonomi dan Bisnis Airlangga)
Introduction: This study aims to determine the effect of green accounting, corporate social responsibility and profitability on firm value.